2021
DOI: 10.3390/atmos12050549
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Levels, Emission Sources and Health Effect of PM2.5-Bound Carbonaceous Particles and Polycyclic Aromatic Hydrocarbons in the City of Kuala Lumpur, Malaysia

Abstract: With increasing interest in understanding the contribution of secondary organic aerosol (SOA) to particulate air pollution in urban areas, an exploratory study was carried out to determine levels of carbonaceous aerosols and polycyclic aromatic hydrocarbons (PAHs) in the city of Kuala Lumpur, Malaysia. PM2.5 samples were collected using a high-volume sampler for 24 h in several areas in Kuala Lumpur during the north-easterly monsoon from January to March 2019. Samples were analyzed for water-soluble organic ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…In this study, BkF was the dominant species presence in particulate PAHs samples for all HT schools with concentration range from 0.64 to 1.84 ng m −3 for indoor and 0.71 to 1.04 ng m −3 for outdoor. The result is consistent with study by Suradi et al [ 18 ] which detected BkF out of 13 measured PAHs species, as the dominant species at Kuala Lumpur City Hall (DBKL) with the mean concentration 0.42 ng m −3 . On the other hand, ACP was the highest species found in the indoor samples of school L1 and L2 with the concentration of 0.91 ng m −3 and 0.84 ng m −3 , respectively.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, BkF was the dominant species presence in particulate PAHs samples for all HT schools with concentration range from 0.64 to 1.84 ng m −3 for indoor and 0.71 to 1.04 ng m −3 for outdoor. The result is consistent with study by Suradi et al [ 18 ] which detected BkF out of 13 measured PAHs species, as the dominant species at Kuala Lumpur City Hall (DBKL) with the mean concentration 0.42 ng m −3 . On the other hand, ACP was the highest species found in the indoor samples of school L1 and L2 with the concentration of 0.91 ng m −3 and 0.84 ng m −3 , respectively.…”
Section: Resultssupporting
confidence: 92%
“…This study’s findings suggested that PAH sources mainly from vehicular emission and other pyrogenic contributions such as grass, wood, and coal combustion. A similar finding was found in a previous study that reported PAHs compound in Kuala Lumpur may not only originated from urban traffic combustion, but also contributed by coal, grass, and wood burning activities [ 18 ].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations